“Becoming White”: The Problem of Fine Art Neocolonization in Postcolonial Era - Kasiyan, Kasiyan Kasiyan (Humanus, 2022)
One of the crucial-cultural matters experinced by all colonialized nations, not to mention Indonesia, is their incapability in becoming free from the shackles of colonialism syndrome. In terms of Indonesian context, for instance, this problem, can be easily identified almost in every existing layer of its civilization system, not to mention in fine arts, either in its artifact, sociofact or ideofact level that is under the infuence of Western hegemony. For this reason, this particular study focuses on: firstly, describing the construction of Western character hegemony found in fine arts in Indonesia; and secondly, identifying for an outlet from the issue of Western hegemony in Indonesian fine arts. The qualitative-hermeneutic approach was used to explain that phenomenon. The analysis of data found through out this study revealed the following results. West hegemony has become an obsession curse beyond all of desire, in its cultural performance in this postcolonial era. This is what merely called the ‘becoming white’ phenomenon. In Indonesian contexts, the construction of this phenomenon particularly in fine arts world is manifested in its hegemonic historiography embodiment that is dissolved in the Western centric mainstream. Hence, a set of strategic cultural processes are necessary to be conducted for the sake of finding the best solution towards that problem. And one of the processes is by conducting methodological deconstruction over all knowledge epistemology including fine arts knowledge existed and owned by this nation.